Analisis PDR, IPM dan Indikator Sosial sebagai Dasar Penyusunan Strategi Fiskal di Silawesi Tengah - Nur Fadillah; Dwi Farradila; Nina Yusnita Yamin; Andi Chairil Furqan; Betty Betty (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze Gross Regional Domestic Product (GRDP), the Human Development Index (HDI), and social indicators such as open unemployment, poverty, and literacy rates as a basis for developing appropriate fiscal strategies for regions in Central Sulawesi Province. The research method used is a descriptive quantitative approach using secondary data from the Central Statistics Agency (BPS) in 2024. The analysis results reveal quite striking disparities, where regions such as Morowali have very high GRDP per capita due to the dominance of the industrial sector, but have not been accompanied by a commensurate increase in the HDI. Meanwhile, regions such as Parigi Moutong and Donggala still lag behind in economic and social terms. Palu City, as the provincial capital, recorded the highest HDI and literacy rates, but still faces significant unemployment problems. This phenomenon indicates that economic growth has not been able to automatically improve the quality of life evenly. Therefore, a more adaptive and responsive fiscal strategy is needed to address the characteristics of each region, with a focus on strengthening social infrastructure, equitable distribution of basic services, job creation, and optimizing local potential to encourage inclusive and sustainable development in Central Sulawesi.